2008
DOI: 10.1080/17477160802596189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of active and passive recruitment methods used in randomized controlled trials targeting pediatric obesity

Abstract: Objective-Evaluate enrollment numbers, randomization rates, costs, and cost-effectiveness of active versus passive recruitment methods for parent-child dyads into two pediatric obesity intervention trials.Methods-Recruitment methods were categorized into active (pediatrician referral and targeted mailings, with participants identified by researcher/health care provider) versus passive methods (newspaper, bus, internet, television, and earning statements; fairs/community centers/schools; and word of mouth; with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Possible reasons for poor recruitment, and strategies to enhance children' s participation in clinical research, have been discussed in the literature. [56][57][58][59][60][61][62][63][64] Public confidence in clinical research is integral to improving recruitment and participation in research involving children. 65 Better regulation and oversight of research transparency, including consistent posting of results from all clinical research, may help improve public trust.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for poor recruitment, and strategies to enhance children' s participation in clinical research, have been discussed in the literature. [56][57][58][59][60][61][62][63][64] Public confidence in clinical research is integral to improving recruitment and participation in research involving children. 65 Better regulation and oversight of research transparency, including consistent posting of results from all clinical research, may help improve public trust.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment methods can be categorised as active, in which researchers target potentially eligible participants, such as with a targeted letter or referral from a health professional, or as passive, in which researchers inform the whole community using flyers, posters, public events and media. A study from the USA evaluating active versus passive recruitment for parent–child pairs in two child obesity intervention trials [ 8 ] showed that active recruitment methods, such as paediatric referral and targeted mailings, led to a higher number of recruited participants but required significant resources. The Loozit randomised controlled trial also reported the effectiveness of strategies to recruit overweight and obese adolescents aged 13–16 years from the community to a weight management treatment trial [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found that participants recruited through proactive phone calls, compared to participants who made the first contact, were more likely to be racial/ethnic minorities and to have lower education [25]. A cost analysis of recruitment methods for clinic-based pediatric obesity trials found that provider referrals was the most cost-effective, and the combination of provider referrals with targeted mailings the most successful [44]. Our findings support the combined strategy of targeted mailings and provider referrals.…”
Section: Discussionmentioning
confidence: 99%